Comparison of the charge of various gases surrounding a dust particle at mesospheric altitudes - Шынықұлова , Г. Н.; Ашикбаева, А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this paper, the authors consider the charge of a dust particle in the ionosphere, which interacts with plasma particles consisting of various gases. There are described features of the mesosphere and the formation of dust particles at a given height of the ionosphere. The velocity distributions of electrons and ions have been assumed to be Maxwellian, i.e. it is assumed that the plasma medium is in a stationary state. Have been performed for ionospheric plasma at an altitude of 85 km with a temperature of 150◦ К, a concentration of electrons and ions of 10 10 m −3, and an ion frequency of 10 5 s −1 . The article considers spherical particles with the same size. The authors have used OML theory to model the charge of dust particles. The results of calculations constructed graph Maxwell distribution of plasma particles velocity, and the dependence of the potential of different gases on the surface of a spherical dust particles from the ratio of temperatures of electrons and ions.